Applicability of metabolomics to improve sustainable grapevine production - Estêvão, Catarina; Rodrigues, Lénia; Rato, Ana Elisa; Garcia, Raquel; Cardoso, Hélia; Campos, Catarina (Frontiers in Molecular Biosciences, 2024)
Metabolites represent the end product of gene expression, protein interaction and other regulatory mechanisms. The metabolome reflects a biological system's response to genetic and environmental changes, providing a more accurate description of plants' phenotype than the transcriptome or the proteome.Grapevine (Vitis vinifera L.), established for the production of wine grapes, table grapes, and raisins, holds immense agronomical and economic significance not only in the Mediterranean region but worldwide. As all plants, grapevines face the adverse impact of biotic and abiotic stresses that negatively affect multiple stages of grape and wine industry, including plant and berry development pre-and post-harvest, fresh grapes processing and consequently wine quality.In the present review we highlight the applicability of metabolome analysis in the understanding of the mechanisms involved in grapevine response and acclimatization upon the main biotic and abiotic constrains. The metabolome of induced morphogenic processes such as adventitious rooting and somatic embryogenesis is also explored, as it adds knowledge on the physiological and molecular phenomena occurring in the explants used, and on the successfully propagation of grapevines with desired traits. Finally, the microbiome-induced metabolites in grapevine are discussed in view of beneficial applications derived from the plant symbioses.